2021
DOI: 10.22541/au.161169908.87361055/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nonadaptive radiation of the gut microbiome in an adaptive radiation of Cyprinodon pupfishes with minor shifts for scale-eating

Abstract: Adaptive radiations offer an excellent opportunity to understand the eco-evolutionary dynamics of gut microbiota and host niche specialization. In a laboratory common garden, we compared the gut microbiota of two novel trophic specialists, a scale-eater and a molluscivore, to a set of four outgroup generalist populations from which this adaptive radiation originated. We predicted an adaptive and highly divergent microbiome composition in the specialists matching their rapid rates of craniofacial diversificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Craniofacial morphology is one of the rapidly diversifying traits in this system, suggesting that divergence in daam2 may play a role in the shared craniofacial divergence of the two scale-eating species. Similarly, usp50 functions in protein metabolism and deubiquination [35] and may play a role in shared metabolic adaptations to the higher-protein content of a scale-eating or snail-eating diet (also note microbiome divergence of C. desquamator with increased prevalence of collagenase-digesting bacteria when reared in a common garden:[36]). atp8a1 is an ion transporter [37], znf214 is a transcription binding factor, and the ten unannotated variants were not associated with lower jaw size variation in a previous genome-wide association study of the radiation (Richards et al 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Craniofacial morphology is one of the rapidly diversifying traits in this system, suggesting that divergence in daam2 may play a role in the shared craniofacial divergence of the two scale-eating species. Similarly, usp50 functions in protein metabolism and deubiquination [35] and may play a role in shared metabolic adaptations to the higher-protein content of a scale-eating or snail-eating diet (also note microbiome divergence of C. desquamator with increased prevalence of collagenase-digesting bacteria when reared in a common garden:[36]). atp8a1 is an ion transporter [37], znf214 is a transcription binding factor, and the ten unannotated variants were not associated with lower jaw size variation in a previous genome-wide association study of the radiation (Richards et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Propionates and other short chain fatty acids are common microbiome metabolites [102]. A recent microbiome study in lab- reared populations found that C. desquamator microbiomes appear enriched for Burkholderiaceae bacteria that can digest collagen, further supporting an adaptive role for microbiomes in the radiation [73].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations